Conceptual design and thermodynamic assessment of an integrated sCO2 Waste-Heat recovery system for sustainable co-generation of ammonia - Hamza Ahmed; Tariq Talha; Muhammad Shoaib Ahmed Khan; Usama Perwez; Abdur Rehman Mazhar; Muhammad Rehan Khan; Talha Irfan Khan (Fuel, 2027)

Enhancing infrastructure resilience in stratified soft soils: 3D modeling of progressive strength degradation in pile-supported retaining walls - Muhammad Israr Khan; Jianbo Fei; Xiangsheng Chen; Yue Chen; Muhammad Hamza (European Journal of Environmental and Civil Engineering, 2026)

Molecular epidemiology and resistance modulation of Streptococcus spp. in subclinical goat mastitis in Pakistan - Ashraf Ali; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Hamza Rasheed; Maria Batool; Kehkshan Shahid; Gulbaz Anwar; Mahpara Safdar (Small Ruminant Research, 2026)

Satellite-anchored UAV sensing system for high-resolution soil moisture mapping - Muhammad Ibrahim Rana; Hamza Rafique; Hassan Jaleel (Computers and Electronics in Agriculture, 2026)

A 25-year analysis of intracerebral hemorrhage mortality trends among patients with essential hypertension: Insights from the CDC WONDER database (1999–2024) - Mohammad Hamza Bin Abdul Malik; Muhammad Arham; Muhammad Awais Bin Abdul Malik; Allah dad; Anfal Hamza; Ayesha Ihsan; Tahira Nazir; Faseeh Haider; Ali Haq; Muhammad Salman Sabri (Next Research, 2026)

Adsorption-desorption nexus of biowaste-derived biochars towards potentially toxic elements: Unveiling challenges and paving paths for the large-scale mining and industrial soil applications - Javed Nawab; Ruby; Amir Hamza; Muhammad Waqas; Cosimo Magazzino; Matthias Kleinke; Irfan Ullah (Biomass and Bioenergy, 2026)

Investigational Studies of Mn/Ag/Graphene@PANI Quaternary Composite for Ni(II) Removal Efficiency - Muhammad Saleem; Aamir Rasheed; Aneeqa Surkhab; Mahnoor Shireen; Rana Hamza Zafar (Water, Air, & Soil Pollution, 2026)

Molecular insights, resistance profiling, and in silico structural modeling of extended-spectrum beta-lactamase-producing E. coli in camels - Mahpara Safdar; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Kehkshan Shahid; Maria Batool; Gulbaz Anwar; Hamza Rasheed; Ashraf Ali (Veterinary Research Communications, 2026)

Phytochemical profiles and therapeutic potentials of Thalictrum species in Africa and Asia: a structured review with evidence quality assessment and strategic framework for drug discovery - Sagir Mustapha; Lukman Mustapha; Suciati Suciati; Kayatri Govindaraju; Irma Wati Ngadimon; Muhammad Luqman Nordin; Mustapha Mohammed; Hamza Lawal; Hasiya Usman Jibrilla; Nabil Abdulkarim; Ahmad Khusairi Azemi (Plant Biosystems, 2026)

Harnessing the biocontrol potential of Trichoderma: Mechanisms, applications, and future prospects in sustainable crop protection - Muhammad Faiq Irfan; Amjad Ali; Rabia Noor; Aniqa Ijaz; Hamza Rafiq; Faisal Shafiq Mirza (Physiological and Molecular Plant Pathology, 2026)

A Novel Green MIP-202/TOCNF Composite Aerogel for Rapid PFAS Adsorption: Performance, Kinetics, and Mechanistic Insights - Muhammad Hamza; Muhammad Waqas; Islam Elsayed; Gregory Schueneman; El Barbary Hassan (Journal of Environmental Chemical Engineering, 2026)

Graft incompatibility in fruit trees in early detection: integrating physiological, molecular, and technological approaches - Muhammad Hamza; Dilek Soysal; Izhar Ullah; Yaqoob Sultan; Erol Aydin; Hüsnü Demirsoy; Heba I. Mohamed (Planta, 2026)

Self-powered electrochemical glucose sensing enabled by zirconium holmium oxide/MXene/graphene nanocomposites with integrated energy storage - Nora Mobark Farhan; Saba Khalil; M.S. Al-Buriahi; Muhammad Ali Hamza Shahbaz; Nissren Tamam; Amir Muhammad Afzal; Abhinav Kumar; Sohail Mumtaz (Analytica Chimica Acta, 2026)

An Innovative conceptual framework to identify the potential sites for rainwater harvesting in arid regions - Muhammad Shahid; Muhammad Waseem; Khalil Ur Rahman; Sajjad Haider; Hamza Farooq Gabriel (Environment, Development and Sustainability, 2026)

Concerns regarding the article “Comparative clinical observations following introduction of a new polyvalent antivenom for snakebite envenoming in northern Nigeria” by Hamman et al. Toxicon 266 (2025) 108510 - Muhammad Hamza; Garba Ilyasu; Hamman A. Nicholas; Mohammed B. Saiyejo; Titus B. Dajel; Abubakar B. Saidu; Bashir Dansanda; Hayatuddeen Saed; Kabir S. Tahir; Bashir Z. Chedi; Abdulrazaq G. Habib (Toxicon, 2026)

Numerical Analysis of Altitude Effects on Single-Cylinder Two-Stroke UAV Engine Performance - Muhammad Nouman Rashid; Faiq Said; Syed Ghafoor Shah; Muhammad Bilal; Hamza Sultan; Muhammad Qail (Next Research, 2026)

Evaluating the effect of Iron biofortification on nutraceutical and aromatic profiles of cereal grains: A case study of pearl millet - Hamza M.A. Abaker; Sulafa B.H. Hashim; Haroon Elrasheid Tahir; Muhammad Arslan; Gustav Komla Mahunu; Zhuhai Li; Xiaodong Zhai; Abdalbasit Adam Mariod; Mohammad Rezaul Islam Shishir; Magdi Ali Osman Mohammed; Ahmed Gaafar Mohammed Elgorashi; Alaa K.M. Khogly; et al. (Food Chemistry, 2026)

Deciphering the role of potato peel on sunflower hybrids growth, photosynthesis, osmoregulation, oxidative defense and ion uptake under salinity - Sundas Fatima; Aasma Tufail; Muhammad Bilal Hafeez; Samreen Nazeer; Noreen Zahra; Fatima Latif; Sabina Asghar; Muhammad Ahsan; Muhammad Hamza; Muhammad Zubair Akram (Biocatalysis and Agricultural Biotechnology, 2026)

Alleviation of salinity induced toxicity in quinoa (Chenopodium quinoa Willd.) through ascorbic acid application - Muhammad Faisal Maqsood; Tahira Fatima; Rehana Kanwal; Fozia Farhat; Muhammad Shahbaz; Muhammad Jamil; Saba Shafqat; Muhammad Asif; Muhammad Hamza Maqsood; Maryam Tariq; Usman Zulfiqar; Muhammad Ahmad (Biocatalysis and Agricultural Biotechnology, 2026)

Can baxdrostat redefine blood pressure control in resistant and uncontrolled hypertension? a systematic review, meta-analysis, and trial sequential analysis - Bilal Wazir Khan; Muhammad Yahya; Hamza Wazir Khan; Miguel Alejandro Rivas Perez; Tayyaba Ikram Qazi; Humaira Obaid; Muhammad Mustafa Khan; Muhammad Maaz Amjad; Muhammad Faaz Khan; Aneeq Mahmood Khan; Muhammad Junaid Khan; Sajjad Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Factors influencing circular economy adoption in Pakistan’s construction industry - Rai Waqas Azfar; Mohsin Shah; Mughees Aslam; Muhammad Sohail Anwar Malik; Hamza Alam (Environment, Development and Sustainability, 2026)

Mechanistic insights into combined effect of magnetic field and transglutaminase on the modification of peanut oleosomes-filled myofibrillar protein emulsion gels - Muhammad Hamza Sardar; Maria Rahman; Taskeen Zafar; Chaoyi Duan; Mingfeng Xu; Sida Fu; Rongrong Yu (Innovative Food Science & Emerging Technologies, 2026)

Exploration of molecular mechanisms responsible for arthritis alleviating attributes of Calliandra haematocephala extracts - Inaam Ur Rehman; Taha Muhammad; Abir Abdullah Alamro; Eman Hassan Alshehri; Hamza Ahmad Odeibat; Rodney B. Luwor; Adrian A. Achuthan; Mohammad Saleem; Mohamed Farouk Elsadek (Inflammopharmacology, 2026)

Sustainable development of novel lime marble dust composite compressed earth blocks: mechanical and durability performance evaluation - Salman Farooq; Zia Ul Islam; Muhammad Isa Khan; Hamza Sajjad (Innovative Infrastructure Solutions, 2026)

Waste cooking oil conversion into multifunctional additives to develop economic bio-lubricant - Muhammad Sikandar; Javaria Ashiq; Ali Raza; Ameer Hamza; Mohammad Owais Aftab; Misbah Murshid; Maryam Rizwan; Azra Akbar; Muhammad Javid Iqbal (Sustainable Chemistry and Pharmacy, 2026)

Biochemical Characterization and Phylogenetic Diversity Assessment of Onion (Allium Cepa L.) Genotypes - Samira Habib; Syed Dilnawaz Ahmad Gardezi; Ahmed Mahmoud Ismail; Safira Attacha; Sajid Fiaz; Muhammad Imran Hamza; Armghan Shehzad; Shazia Arif (Plant Molecular Biology Reporter, 2026)

Safety and tolerability of the ACE-inhibitor lisinopril among Nigerian adults with HIV: preliminary pilot data from a randomized clinical trial - Faisal S. Dankishiya; Hamza Muhammad; Usman J. Wudil; Baba M. Musa; Liping Du; Ibrahim A. Adam; Aima A. Ahonkhai; Anna M. Burgner; Aishatu M. Nalado; Mahmoud U. Sani; Aliyu Abdu; Bryan E. Shepherd; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Synthesis and structure–activity relationship studies of 1,2,4-triazole–benzoxazepine hybrids as α-glucosidase inhibitors: molecular docking and biological evaluation - Muhammad Ashram; Ahmed Al-Mustafa; Almeqdad Y. Habashneh; Hamza I. Al-Hrerat; Mahmoud A. Al-Sha’er; Firas F. Awwadi; Islam Ashram (Medicinal Chemistry Research, 2026)

E-Waste-Derived Highly Sensitive and Scalable Flexible Fractal Capacitive Sensors-Based Smart Wearable Joint Orthosis System for Post-Surgical Rehabilitation - Amna Tariq; Nida Iqbal; Rimsha Sarwar; Asma Latif; Saman Iqbal; Muhammad Hamza Zulfiqar (Journal of Medical and Biological Engineering, 2026)

Nutritional profile, phytochemicals, and bioactivities of the Himalayan herbal tea plant Persicaria amplexicaulis - Amna Mustafa; Ansar Mehmood; Imtiaz Hussain; Muhammad Imran Hamza; Khawaja Shafique Ahmad; Mushtaq Ahmad (Plant Biosystems, 2026)

Comment on “Validity study of the Turkish version of the Mini-Addenbrooke’s cognitive examination in mild cognitive impairment and Alzheimer’s disease” - Marwa Mehak; Warda Fatima Shafee; Muhammad Hamza Shafee; Bilal Ahmad (Acta Neurologica Belgica, 2026)

Efficacy of aripiprazole and valbenazine in the treatment of tourette syndrome: a systematic review and meta-analysis of randomized controlled trials - Muneeb Ahmad Muneer; Ume Habiba; Shajjia Shehzad; Washija Batool; Dawood Shah; Zain Shahzad; Muhammad Khizar Kirmani; Zohaib Hassan Siddiqui; Areeb Amjad; Ameer Hamza; Muhammad Faizan Khan; Fahad Siddique Butt; et al. (Acta Neurologica Belgica, 2026)

Leveraging Extremophyte Adaptations as a Roadmap for Crop Design for Arid Lands - Mohsin Tanveer; Lei Wang; Hamza Tariq; Muhammad Talha Ramzan; Alisdair R. Fernie; Jaume Flexas; Sergey Shabala; Josep Peñuelas (Global Change Biology, 2026)
Anthropogenic climate change is driving a convergence of rapid soil aridification and secondary salinization that threatens to degrade over half of the world's arable land. As conventional glycophytic crops reach their physiological limits, global food security depends on decoding the evolutionary adaptations of extremophytes. This review synthesizes the functional traits and ecosystem‐level impacts of extremophytes, the native flora of these marginal environments, and evaluates their potential as a biophysical buffer against land degradation. Here, we identify two cornerstone strategies that allow these plants to thrive where others fail: (i) the precise spatiotemporal orchestration of reactive oxygen species (ROS) as critical signaling molecules for developmental plasticity; and (ii) the active recruitment of stress‐protective microbiomes via targeted exudation, effectively transforming barren soil into a functional ecosystem. We argue that integrating extremophytes into diversified agroecosystems, through intercropping, phytoremediation rotations, and circular bioeconomy models, offers quantifiable results to enhance ecosystem multifunctionality and sustainably intensify production on degrading lands. By bridging profound mechanistic discovery with ecological engineering, this perspective provides an actionable plan for translating extremophyte biology into crops capable of withstanding a drier future.

Transplantation of Ru265-treated mitochondria enhances the therapeutic impact on skeletal muscle ischemia-reperfusion injury - Saima Barki; Fazal Wahid; Shafia Khan; Laiba Tariq Abbasi; Zarrish Rubab; Ameer Hamza; Farman Ullah; Khadeeja Ahsan; Durre Shehwar; Muhammad Rizwan Alam (Molecular and Cellular Biochemistry, 2026)

SARS-CoV-2 antibody responses during the omicron wave in kano, nigeria: Implications for strengthening future vaccine strategies - Bilkisu Ahmed; Jamilu Abubakar Bala; Taysir Ramadan Hafiz; Isah Abubakar Aliyu; Abdulhadi Sale Kumurya; Ibrahim Muhammad Badamasi; Hayatu Saidu; Muhammad Adamu Abbas; Auwal Idris Kabuga; Alhassan Sharif Abdullahi; Bashiru Garba; Al-Mukhtar Yahuza Adamu; et al. (Next Research, 2026)

Radiological contamination in soils near the world's largest rare earth minerals producing region and their impacts on human health: A summary analysis - Amir Hamza; Faisal Khan; Javed Nawab; Junaid Ghani; Sajid Ali; Yaseen Laghari; Luo Xin; Niaz Muhammad; Jing Cui; Zhenggui Wei (Journal of Environmental Radioactivity, 2026)

Optimized identification of glacial lake outburst flood hazard using multi-criteria decision analysis - Aniqa Murtaza; Muhammad Waqar Saleem; Hamza Farooq Gabriel; Khalil Ur Rahman; Zafar Iqbal; Deqiang Mao (Hydrological Sciences Journal, 2026)

Root inoculation with Trichoderma harzianum primes metabolic and stress-response pathways underlying growth and resistance in Brassica rapa - Bilal Ahmad; Aleena Alam; Sohail Abbas; Muhammad Ameer Hamza; Khalid Ali Khan; Hamed A. Ghramh; Raul Narciso C. Guedes; Qiyun Li; Rizhao Chen (Pesticide Biochemistry and Physiology, 2026)

Electrodialysis for sustainable water desalination: Principles, applications, challenges, and future directions - Subhan Mahmood; Numan Mahmood; Muhammad Usman Liaquat; Faizan Ikhlaq; Hamza Shehzad; Shun Yao (Journal of Environmental Chemical Engineering, 2026)

A review of ice accretion, detection, and mitigation methods for the gondola infrastructure application - Hamza Asif; Muhammad S. Virk; Jan-Arne Pettersen; Pourya Pourhejazy (Cold Regions Science and Technology, 2026)

Comparative insights into molecular characterization and resistance profiling of methicillin-resistant Staphylococcus aureus across dairy livestock in Pakistan - Muhammad Ijaz; Maria Batool; Muhammad Umar Javed; Hamza Rasheed; Arslan Ahmed; Ali Abdullah Jabir; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2026)

Integrating CMIP6 climate projections with community-based vulnerability assessment for climate resilience in Haripur, Pakistan - Syed Shujaat Ali; Sabahat Isha; Hamza Paracha; Abdullah Nadeem; Muhammad Atiq Ur Rehman Tariq (Theoretical and Applied Climatology, 2026)

Remote sensing-based 2D hydrodynamic modeling and assessment of the 2014 flood in the Jhelum river basin - Rizwan Mansha; Sajjad Haider; Muhammad Azmat; Hamza Farooq Gabriel; Fahim Ullah (Modeling Earth Systems and Environment, 2026)

Integrating machine learning and deep learning for enhanced landslide susceptibility and propagation dynamics in Northwestern Pakistan - Hafiz Ullah; Wei Wang; Hamza Daud; Muhammad Afaq Hussain; Nafees Ali (Bulletin of Engineering Geology and the Environment, 2026)

Exploring the efficacy of a novel cannabidiol and bevacizumab combination in non-small cell lung cancer - Abdul Qadir; Zurqa Khalid; Ayesha Kashmala Ghauri; Muhammad Hamza Dawood; Usama Manzoor; Habib Ur Rehman (DARU Journal of Pharmaceutical Sciences, 2026)

Characterization and fungicidal sensitivity of Phytophthora species causing citrus gummosis in Pakistan - Hadeed Ahmad; Muhammad Wahab; Muhammad Atiq; Muhammad Usman; Muhammad Hamza Shahid; Muhammad Usman Ali; Owais Iqbal; Muhammad Luqman Aleem; Qurban Ali; Nasir Ahmed Rajput (Physiological and Molecular Plant Pathology, 2026)

Experimental and predictive advancements in hydrogen enriched compressed natural gas spark ignition engines: a critical review - Muhammad Farhan; Hamza Ahmad Salam; Muhammad Ihsan Shahid; Tianhao Chen; Qiuhong Xiao; Long Jiang; Anas Rao; Xin Li; Fanhua Ma (Fuel, 2026)

Fabrication, Characterization, and Effects of CuS Nanoparticles as Nano-Fertilizers on the Morphological, Biochemical Responses, and Bioaccumulation of Metal in Soybean (Glycine Max L.) and Sesame (Sesamum Indicum L.) - Jehangir Khan; Anila Sajjad; Khalid Khan; Ihsan Ullah; Syed Hamza Safeer; Muhammad Zia (Journal of Soil Science and Plant Nutrition, 2026)

Characterization of aquifer hydraulics and pumping well yield for supplemental paddy crop irrigation using pumping tests in Perak, Malaysia - Naseem Akhtar; Muhammad Izzuddin Syakir; Syahidah Akmal Muhammad; Aznan Fazli Ismail; Mohamad Shaiful Md. Yusuff; Leila Bouida; Hamza Mohamed Flafel; Pahmi Husain; Mohammed Benaafi; Taskin Ahmed; Mohammad Muqtada Ali Khan (Paddy and Water Environment, 2026)

From micro-pixels to macro-performance: An explainable machine learning framework for xanthan gum-stabilized expansive soils via AI-assisted trainable weka segmentation - Muhammad Hamza; Wen-Bo Chen; Jing-Cheng Teng; Han-Jiang Lai; Akhtar Rehman; Muhammad Israr Khan (Journal of Cleaner Production, 2026)

Subject: Concerns regarding the article “comparative clinical observations following introduction of a new polyvalent antivenom for snakebite envenoming in northern Nigeria” by Hamman et al. Toxicon 266 (2025) 108510 - Garba Iliyasu; Saidu B. Abubakar; Nicholas A. Hamman; Titus B. Dajel; Muhammad Hamza; Basheer Z. Chedi; Abdulrazaq G. Habib (Toxicon, 2025)

Subject: Concerns regarding the article “comparative clinical observations following introduction of a new polyvalent antivenom for snakebite envenoming in northern Nigeria” by Hamman et al. Toxicon 266 (2025) 108510 - Muhammad Hamza; Titus B. Dajel; Nicholas A. Hamman; Saidu B. Abubakar; Garba Iliyasu; Basheer Z. Chedi; Abdulrazaq G. Habib (Toxicon, 2025)

Energy transition, globalization, and FDI: Pathways to achieve sustainable development goals in T-MEC countries - Hong Wu; Kashif Raza Abbasi; Muhammad Irfan; Stefania Pinzon; Amir Hamza (Gondwana Research, 2025)

Analysis of exhaust heat recovery and hydrogen production by steam methane reforming under different operating conditions of the HCNG engine - Muhammad Ihsan Shahid; Muhammad Farhan; Anas Rao; Muhammad Saddam Hussain; Xianlei Zhu; Hamza Ahmad Salam; Tianhao Chen; Xin Li; Fanhua Ma (Fuel, 2025)

Bridging the gap: Advancing behavioral economics and climate change research in developing countries - Hamza Umer; Muhammad Salar Khan (Energy and Climate Change, 2025)

Mapping the non-coding RNA landscape in ataxia telangiectasia: a scoping review of ATM dependent miRNA and lncRNA dysregulation - Muhammad Junaid Iqbal; Usman Ameen; Hamza Tanveer; Laraib Israr; Anastasia Ricci; Gianluca Morganti; Muhammad Jawad Khan; Michele Menotta (Molecular Biology Reports, 2025)
Ataxia-Telangiectasia (A-T) is caused by biallelic Ataxia-Telangiectasia Mutated (ATM) protein mutations and is hallmarked by neurodegeneration, immunodeficiency and cancer susceptibility. Emerging work suggests that non-coding RNAs are integral to the ATM driven DNA damage response, yet the scope of non-coding RNA perturbation in A-T has not systematically mapped. This study is done to chart and synthesize all primary evidence on ncRNA dysregulation in A-T and to identify mechanistic gaps and research priorities. The evidence base comprises a total of five studies focused exclusively on microRNAs and long non-coding RNAs. Baseline sequencing of 20 patients revealed consistent downregulation of miR-195-5p, miR-30a-5p and miR-342-3p. Low dose γ-irradiation of ATM-null lymphoblastoid cell lines produced an exaggerated bidirectional shift (8 microRNAs upregulated, 6 downregulated) versus wild-type, whereas primary T-cells showed largely ATM independent rises of miR-34a-5p and miR-182-5p. A lymphoblastoid cell lines study distinguished 22 recessive or dominant radiation-responsive microRNAs. Long non-coding RNAs profiling identified 149 transcripts that require functional ATM for induction and three uniquely upregulated in A-T cells. No circular RNA study in A-T is observed till date. The ncRNA research in A-T is nascent with five studies present a miRNA dysregulation and an ATM-dependent lncRNA surge that is lost in A-T, but leave circRNAs, neuronal tissues and functional validation unexplored. Intermediate dose stress models, total and small RNA-seq under DNA damage and oxidative stress, and CRISPR rescue/knockout screens in patient derived organoids are immediate priorities for exploring the role of ncRNAs as therapeutic targets in A-T.

Mechanistic insight into inflammatory and oxidative stress ameliorating attributes of Atriplex crassifolia 70% ethanol extract against complete Freund’s adjuvant-induced arthritis - Jawaria Khurshid; Anam Iftikhar; Hamza Ahmad Odeibat; Eman Hassan Alshehri; Kiran Aslam; Maria Jaleel; Aymun Jawed; Muhammad Khalid Saeed; Rodney Luwor; Taha Muhammad; Mohammad Saleem; Mohamed Farouk Elsadek (Inflammopharmacology, 2025)

The impact of germination time on nutritional and antioxidant properties of selected cereals - Fahid Nazir; Hamza Zahid; Muhammad Riaz; Yahya Mushtaq; Natasha Amjad; Humaira Iqbal; Muhammad Rizwan Majeed; Shazia Kousar; Muhammad Ahmad Mudassir (Cereal Research Communications, 2025)

Comparative clinical observations following introduction of a new polyvalent antivenom for snakebite envenoming in northern Nigeria - Nicholas A. Hamman; Titus B. Dajel; Mohammed B. Saiyejo; Saidu B. Abubakar; Bashir Dansanda; Hayatu Saeedu; Kabiru Tahir; Muhammad Hamza; Garba Iliyasu; Basheer Z. Chedi; Abdulrazaq G. Habib (Toxicon, 2025)

Synergistic PMS activation by SnBi@ZrC under visible light for enhanced organic pollutant removal - Rana Mohsin Ali; Jie Wang; Tianhong Zhou; Yue Tian; Muhammad Usman; Hamza Khaliq; Muhammad Adnan; Zunaira Nasir; Ghulam Abbas Ashraf; Yusuke Yamauchi (Journal of Water Process Engineering, 2025)

Sunlight responsive photo-oxidation of methylene blue dye using MgO/MnO2 nanoparticles - Hamza Laksaci; Nassima Djihane Zemani; Omar Khelifi; Muhammad Saeed; Badreddine Belhamdi; Abdelaziz Arroussi; Mohamed Trari (Colloids and Surfaces C: Environmental Aspects, 2025)

3D printing of high-performance Ag/BaTiO3 ceramic-polymer piezoelectric sensors for biomedical applications - Muhammad Hamza; Qudsia Kanwal; Muhammad Irfan Hussain; Wei Peng; Bin Wang; Zhiyuan Liu; Changyong Liu; Zhangwei Chen (Chemical Engineering Journal, 2025)

Bacillus species compatibility enhances VOC-mediated systemic resistance against Botrytis cinerea - Abdur Rashid Khan; Qurban Ali; Xuxiang Wu; Sheng Chen; Muhammad Ayaz; Hamza Tariq; Muhammad Saqib Bilal; Li Li; Sunil Mundra; Qin Gu; Huijun Wu; Xiaobo Li; et al. (World Journal of Microbiology and Biotechnology, 2025)

Jasmonic Acid: A Key Elicitor of Cold Stress Tolerance in Horticultural Crops - Izhar Ullah; Muhammad Hamza; Noor ul Ain; Heba I. Mohamed; Murad Muhammad; Yaqoob Sultan; Muskan Alam Khan; Abdul Basit (Journal of Plant Growth Regulation, 2025)

Design and development of industrial prototype of spot specific orchard sprayer using ultrasonic sensing system and advanced pressure control mechanism - Arshed Ahmed; Shoaib Rashid Saleem; Muhammad Naveed Tahir; Shahram Hamza Manzoor; Qamar Zaman; Zhao Zhang; Rashed Ahmed (Computers and Electronics in Agriculture, 2025)

Role of aqueous fenugreek (Trigonella foenum-graecum) extract against DBP-induced renal and adrenal pathologies in male rats - Hifsa Shaheen; Sajida Batool; Fatima Iram; Saira Batool; Tahira Almas; Ameer Hamza; Asifa Ijaz; Samar Ambreen; Hafiz Muhammad Uzair (Journal of Molecular Histology, 2025)

Image segmentation and machine learning modelling for water status determination and precision irrigation management - Hamza Salah Ud Din; Aqib Iqbal; Fazal Jalal; Awais Ahmad; Muhammad Haris Paracha; Shah Fahad; Zafar Hayat Khan; Shah Saud; Taufiq Nawaz (Journal of Crop Science and Biotechnology, 2025)

Debris flow susceptibility and propagation modeling: a deep learning and flow-R framework - Muhammad Khalid; Muhammad Zulkarnain bin Abd Rahman; Jabir Hussain Syed; Nafees Ali; Hamza Daud; Muhammad Afaq Hussain; Muhammad Safwan Ruslan; Omar Farouk Fauzi (Bulletin of Engineering Geology and the Environment, 2025)

Urban walkability assessment: methods and implications for city planning - Hamza Chaudhary; Shakeel Mahmood; Yuping Su; Muhammad Sajid Mehmood; Muhammad Irfan Ahamad (Environment, Development and Sustainability, 2025)

Comprehensive assessment of port resilience: A three-stage cycle approach - Yuanyuan Wu; Jiaqi Yang; Min Tu; Muhammad Hamza Naseem (Regional Studies in Marine Science, 2025)

Biofumigation with carvacrol disrupts membrane integrity and metabolic homeostasis in yam leaf spot pathogen Alternaria alternata - Hamza Tariq; Wenwu Zou; Lanning Wang; Jingkun Lv; Abdur Rashid Khan; Muhammad Saqib Bilal; Danyu Shen; Daolong Dou (Pesticide Biochemistry and Physiology, 2025)

Predicting ground-level PM 2.5 using high-resolution satellite imagery and machine learning algorithms with ground-based validation - Muhammad Hamza Tariq; Musawar Hussain; Muhammad Mahad Khaliq; Talha Saeed; Michael Howard Bergin; Muhammad Fahim Khokhar (International Journal of Remote Sensing, 2025)

Investigating the development and success of Spodoptera Frugiperda (Lepidoptera: Noctuidae) on various wheat varieties: an age-stage specific life table analysis - Hamza Latif; Muhammad Arshad; Muhammad Irfan Ullah; Gulfam Yousaf; Nahdia Perveen; Wafa Abdullah Hamad Alkherb; Mohammed Ali Alshehri; Samy M. Sayed (International Journal of Tropical Insect Science, 2025)

Enhanced electrochemical performance of MoP2-based supercapacitor electrodes through doping with transition, post-transition, and rare earth metals - Mudassar Maraj; Mir Rehman Shabbir; Faisal Ali; Muhammad Hamza Naseer; Ali Haider Bhalli; Sarmad Ali; Nian Li; Xiuhong Li; Zhenyang Wang (Fuel, 2025)

Exploring evolutionary perspectives and antibiogram analysis of biofilm-forming Staphylococcus aureus in goat mastitis - Muhammad Umar Javed; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Ali Abdullah Jabir; Maria Batool; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2025)

A framework for addressing water–rock interaction (WRI) for sustainable water resources development using various simulation models: Review - Naseem Akhtar; Abdassalam A. Azamzam; Saleh Ali Tweib; Hamza Mohamed Flafel; Dani Wijaya; Leila Bouida; Pahmi Husain; Shahwaz Khan; Mohd Talha Anees; Muhammad Irman Khalif Ahmad Aminuddin; Shubham Sharma; Rajesh Singh; et al. (Environment, Development and Sustainability, 2025)

First report of Curvularia hawaiiensis causing leaf spot disease of grape in Pakistan - Muhammad Usman Ali; Muhammad Wahab; Muhammad Atiq; Muhammad Usman; Owais Iqbal; Muhammad Hamza Furqan; Ahmad Nawaz; Hamza Tariq; Ghalib Ayaz Kachelo; Nasir Ahmed Rajput (Journal of Plant Pathology, 2025)

A review on supercapacitors: Development trends, challenges, and future perspectives - Iqbal Singh; Rohit Sharma; Amardeep kaur; Dinesh Pathak; Anupinder Singh; Muhammad Hamza; Mehtab Singh; Ajay Vasishth (Next Research, 2025)

Machine learning approach for photocatalysis: An experimentally validated case study of photocatalytic dye degradation - Hassan Ali; Muhammad Yasir; Hamza Ul Haq; Ali Can Guler; Milan Masar; Muhammad Nouman Aslam Khan; Michal Machovsky; Vladimir Sedlarik; Ivo Kuritka (Journal of Environmental Management, 2025)

Unravelling the promotional roles of MoS2 in enhancing photo-activity of ZnCdS for photo-treatment of wastewater containing tetracycline (TC) - Kim Hoong Ng; Muhammad Hamza; Sin Yuan Lai; Nathasya Imanuella; Lian See Tan; Chao-Lin Liu; Hsien-Tsung Wu (Environmental Research, 2025)

Interesterification of waste cooking oil via microwave irradiation for glycerol-free biodiesel production - Muhammad Umer Qadeer; Muhammad Ayoub; Muhammad Hamza Nazir; Muhammad Asad Javed; Zulqarnain; Imtisal Zahid; Mariam Ameen; Farooq Sher; Alhassan Ibrahim (Biomass and Bioenergy, 2025)

Inheritance of Cell Membrane Stability and Yield Components Under Drought and Salinity Stress in Bread Wheat (Triticum aestivum L.) - Sameena Naqi; Aamir Hamid Khan; Rashid Mehmood Rana; Muhammad Imran Hamza; Marcin Kiedrzyński; Muhammad Naveed Tahir; Munir Ahmad; Shah Saud; Shah Hassan; Shah Fahad (Journal of Plant Growth Regulation, 2025)

A review on hydrogen production using decorated metal-organic frameworks by electrocatalytic and photocatalytic water splitting - Rana Adeel Mehmood; Awais Ali Aslam; Muhammad Javid Iqbal; Ali Hamza Sajid; Ameer Hamza; Hina Fatima Tahira; Izaz Ul Islam; Erdal Yabalak (Fuel, 2025)

A Novel Architecture for building rooftop extraction using remote sensing and deep learning - Zeenat khadim Hussain; Jiang Congshi; Muhammad Adrees; Hamza Chaudhary; Rafia Shafqat (Remote Sensing Applications: Society and Environment, 2025)

Mitigative effects of didymin against cadmium-induced renal injury via regulating Nrf-2/Keap-1, apoptosis, inflammation and oxidative stress - Ali Hamza; Sayda Snober Fatima Zadi; Muhammad Zaid Salar; Muhammad Umar Ijaz; Khalid A. Al-Ghanim; Ayesha Ishtiaq (Journal of Trace Elements in Medicine and Biology, 2025)

Effectiveness of newly isolated bacteriophages targeting multidrug-resistant Extraintestinal Pathogenic Escherichia coli strain (TZ1_3) in food preservation and mice health modulation - Youshun Jin; Wei Li; Hafiz Muhammad Hamza Rasool; Xuan Ning; Xuli Ba; Yidan Gao; Xinyu Guo; Tao Ran; Jizhang Zhou (Food Chemistry, 2025)

Improved damage assessment of bridges using advanced signal processing techniques of CEEMDAN-EWT and Kernal PCA - Hamza Ahsan Abdullah; Muhammad Usman Hanif; Muhammad Usman Hassan; Janita Mahnoor Shahid; Shaukat Ali Khan; Ather Ali (Engineering Structures, 2025)

Comparative Analysis of Heavy Metals and Minerals in Dairy and Plant-Based Milk Alternatives Available in Pakistan’s Markets - Aiman Usman; Sadaf Yaqoob; Hamza Shafiq; Mamoona Amir; Muhammad Riaz; Kousar Parveen; Usama Usman (Biological Trace Element Research, 2025)

Advancements in metal selenide nanocomposites for efficient photocatalytic water splitting applications - Zeshan Ali Sandhu; Soha Ghaffar; Muhammad Asam Raza; Noor ul Huda; Sufyan Ashraf; Umair Talat; Areej Chauhdary; Hamza Gulzarab; Abdullah G. Al-Sehemi (Fuel, 2025)

A review of recent advances in green and sustainable technologies for removing 4-nitrophenol from the water and wastewater - Hamza Badamasi; Zain Naeem; Giorgio Antoniolli; Avvaru Praveen Kumar; Abdul Ademola Olaleye; Ismail Shina Sadiq; Naseer Inuwa Durimin-iya; Muhammad Salman Khan (Sustainable Chemistry and Pharmacy, 2025)

Antimicrobial resistance, virulence profiling, and drug repurposing analysis of Staphylococcus aureus from camel mastitis - Hamza Rasheed; Muhammad Ijaz; Arslan Ahmed; Muhammad Muddassir Ali (Veterinary Research Communications, 2025)

Prevalence and genetic diversity of potato virus Y strains in Pakistani potato fields: insights from partial sequence analysis - Muhammad Hamza Shahid; Ghulam Mustafa Sahi; Zunaira Afzal Naveed; Safdar Ali; Muhammad Wahab; Muhammad Sagheer; Azher Mustafa (Journal of Plant Diseases and Protection, 2025)

Multi-scale computational modeling to identify novel chemical scaffolds as trehalose-6-phosphate phosphatase inhibitors to combat Burkholderia pseudomallei - Sara Noor; Mohammad Abdullah Aljasir; Maryam Bashir; Kalsoom Khan; Sajjad Ahmad; Syed Ainul Abideen; Saifullah Khan; Farhan Siddique; Hamza Ahmad; Khudija Ghani; Madiha Iqbal; Muhammad Irfan; et al. (In Silico Pharmacology, 2025)

From stress to resilience: Unraveling the molecular mechanisms of cadmium toxicity, detoxification and tolerance in plants - Iqra Noor; Hamza Sohail; Muhammad Tanveer Akhtar; Jiawen Cui; Zhaogeng Lu; Salma Mostafa; Mirza Hasanuzzaman; Sajjad Hussain; Nan Guo; Biao Jin (Science of The Total Environment, 2024)

Health risk assessment of lead and cadmium exposure from food and snuff in Pakistani population - Hamza Shafiq; Mamoona Amir; Salman Asghar; Aneela Hameed; Muhammad Riaz (Journal of Trace Elements in Medicine and Biology, 2024)

Hydrogen production techniques and use of hydrogen in internal combustion engine: A comprehensive review - Muhammad Ihsan Shahid; Anas Rao; Muhammad Farhan; Yongzheng Liu; Hamza Ahmad Salam; Tianhao Chen; Fanhua Ma (Fuel, 2024)

Characterization and identification of the key volatile and non-volatile substances of Vangueria madagascariensis J.F. Gmel fruits (Kirkir) and exploration of their binding interactions with olfactory and taste receptors using computational chemistry methodology - Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Mohammad Rezaul Islam Shishir; Li Zhihua; Suliman Khan; Abdalbasit Adam Mariod; Hamza A.M. Abaker; Howida Elkheir Ibrahim; Hesham R. El-Seedi; Zou Xiaobo (Food Chemistry, 2024)

Assessment of the ecological status of Cala Iris Bay (Northern Morocco): First characterization and classification according to a multiparametric approach - Hamza Ngadi; Abdelmajid Moumen; Mostafa Layachi; Ghizlane Azizi; Sara Esseffar; Najib El Ouamari; Mourad Baghour; Muhammad Zahid (Environmental Nanotechnology, Monitoring & Management, 2024)

Effect of Bacillus subtilis Supplemented Diet on Broiler’s Intestinal Microbiota and TLRs Gene Expression - Salman Khan; Anam Khalid; Ru Yang; Fatima Khalid; Muhammad Hamza Zahid; Haozhe Liu; Yunhua Zhang; Zaigui Wang (Probiotics and Antimicrobial Proteins, 2024)

Correction to: Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Extraction of bioactive components from date palm waste, various extraction processes and their applications: A review - Imtisal Zahid; Muhammad Hamza Nazir; Muhammad Asad Javed (Biomass and Bioenergy, 2024)

Comprehensive insights on treatment modalities with conventional and herbal drugs for the treatment of duodenal ulcers - Huma Hameed; Jahangir Hussain; Ana Cláudia Paiva-Santos; Muhammad Zaman; Ali Hamza; Irsa Sajjad; Faria Asad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Experimental investigation of the wake of tandem cylinders using pivoted flapping mechanism for piezoelectric flag - Muhammad Mahad Shah; Rizwan Mahmood; Usman Latif; Emad Uddin; Adnan Munir; Ming Zhao; Hafiz Hamza Riaz (Ocean Engineering, 2024)

Photocatalytic applications of A5-mPmH-Zr/CuTiO3 nanocomposite synthesized by simple hydrothermal method - Ghulam Murtaza; Muhammad Saud Khan; Kamran Tahir; Afaq Ullah Khan; Magdi E.A. Zaki; Zainab M. Almarhoon; Abdulaziz A. Alanazi; Hamza S. Al-Shehri; Sameerah I. Al-Saeedi; Hassan M.A. Hassan (Journal of Environmental Chemical Engineering, 2024)

Current outlook on sustainable feedstocks and processes for sustainable aviation fuel production - Imtisal Zahid; Muhammad Hamza Nazir; Ken Chiang; Farid Christo; Mariam Ameen (Current Opinion in Green and Sustainable Chemistry, 2024)

Editing microbes to mitigate enteric methane emissions in livestock - Faheem Ahmed Khan; Azhar Ali; Di Wu; Chunjie Huang; Hamza Zulfiqar; Muhammad Ali; Bilal Ahmed; Muhammad Rizwan Yousaf; Ezi Masdia Putri; Windu Negara; Muhammad Imran; Nuruliarizki Shinta Pandupuspitasari (World Journal of Microbiology and Biotechnology, 2024)

Nuclear integration of MYB36 and APX-1 genes impart heat tolerance in wheat - Hina Firdous; Arfan Ali; Muhammad Mubashar Zafar; Faiz Ahmad Joyia; Muhammad Hamza; Abdul Razzaq; Muhammad Uzair; Sezai Ercisli; Waqas Shafqat Chattha; Mahmoud F. Seleiman; Naeem Khan; Xuefei Jiang (Functional & Integrative Genomics, 2024)

Geospatial intelligence in geotechnical engineering: a comprehensive investigation into SPT-N, soil types, and undrained shear strength for enhanced site characterization - Waqas Hassan; Muhammad Qasim; Badee Alshameri; Arfan Shahzad; Muhammad Hamza Khalid; Sana Ullah Qamar (Bulletin of Engineering Geology and the Environment, 2024)

Retraction Note: Assessing the impact of human capital, renewable energy, population growth, economic growth, and climate change policies on achieving the sustainable development goals - Hamza Akram; Jinchao Li; Muhammad Kahlid Anser; Muhammad Irfan; Waqas Ahmad Watto (Environmental Science and Pollution Research, 2024)

Effect of supplementing epinephrine in maturation media on in-vitro developmental competence of cattle and buffalo oocytes - Abdul Khaliq; Muhammad Ameer Hamza; Talha Ashraf; Ali Husnain; Muhammad Yaseen; Abdul Rehman; Muhammad Binyameen; Muhammad Yasir Zahoor; Amjad Riaz (Theriogenology, 2024)

Computational analysis of fluid dynamics in open channel with the vegetated spur dike - Sohail Iqbal; Muhammad Siddique; Ali Hamza; Nadir Murtaza; Ghufran Ahmed Pasha (Innovative Infrastructure Solutions, 2024)

Bio-perfume guns: Antifungal volatile activity of Bacillus sp. LNXM12 against postharvest pathogen Botrytis cinerea in tomato and strawberry - Abdur Rashid Khan; Qurban Ali; Muhammad Ayaz; Muhammad Saqib Bilal; Hamza Tariq; Mahmoud H. El-Komy; Qin Gu; Huijun Wu; Joachim Vater; Xuewen Gao (Pesticide Biochemistry and Physiology, 2024)

Advanced AI approach for enhanced predictive modeling in reservoir characterization within complex geological environments - Wakeel Hussain; Muhammad Ali; Rakhshanda Sadaf; Harith F. Al-Khafaji; Izhar Sadiq; Chuanyu Hu; Hamza Daud; Salah Alshareef Alkfakey Ahmed (Modeling Earth Systems and Environment, 2024)

Analyzing the Role of Changing Climate on the Variability of Intensity-Duration-Frequency Curve Using Wavelet Analysis - Syed Adnan Shah; Hamza Farooq Gabriel; Muhammad Waqar Saleem; Nuaman Ejaz; Songhao Shang; Deqiang Mao; Khalil Ur Rahman (Water Resources Management, 2024)

Air pollution and climate change as grand challenges to sustainability - Afifa; Kashaf Arshad; Nazim Hussain; Muhammad Hamza Ashraf; Muhammad Zafar Saleem (Science of The Total Environment, 2024)

Transcutaneous Delivery of Dexamethasone Sodium Phosphate Via Microneedle-Assisted Iontophoretic Enhancement – A Potential Therapeutic Option for Inflammatory Disorders - Muhammad Sohail Arshad; Saad Hussain; Saman Zafar; Sadia Jafar Rana; Tahir Ali Chohan; Muhammad Hamza; Kazem Nazari; Zeeshan Ahmad (Pharmaceutical Research, 2024)

ANN and regression based quantification framework for climate change impact assessment on a weak transmission grid of a developing country across Horizon 2050 plus - M. Mahad Malik; Hamza Waheed Asim; Syed Ali Abbas Kazmi; Kamran Mujahid; Muhammad Waleed Ansari (Environment, Development and Sustainability, 2024)

Water resource management and flood mitigation: hybrid decomposition EMD-ANN model study under climate change - Nisar Ahmad; Xu Yi; Muhammad Tayyab; Muhammad Hamza Zafar; Naureen Akhtar (Sustainable Water Resources Management, 2024)
The growing population and the rise in urbanization have made managing water a critical concern around the world in recent years. Globally, flooding is one of the most devastating natural disasters. Flood risk mitigation relies heavily on accurate and consistent streamflow forecasts. Pakistan Upper Indus Basin (UIB) is most vulnerable to flooding. Floods have become more frequent in recent decades. UIB can be divided into sub-regions due to its landscape variability, and its collective impact is most prominent in the Massam region. UIB hydrological and meteorological station observations have been used to study seasonal hydro-meteorological variations. To predict flooding, this study proposes a hybrid model combining artificial neural networks as multi-layer perceptron (MLPs) in feed-forward mode, along with empirical mode decomposition (EMD). Data collected by the surface-water hydrology project and Pakistan Meteorological Department from 1960 to 2012, 1969 to 2012, and 1972 to 2012 have been utilized from 17 locations. Statistical parameters and Nash–Sutcliffe Efficiency were measured to analyze the model’s prowess. As a result, decomposition-based models perform better than AI-based models when it comes to prediction accuracy. MLPQTP-EMD performed exceptionally better than competing AI models. The results are further validated by performing a peak value analysis during the flooding season (June–September) achieving a remarkable 91.3% score adding a 5.6% increase by EMD for input data achieving 39.3–32.3% statistical indices scores.

Comparison of Seepage Evaluation Methods for Earth-Filled Embankments: A Case Study of Sukian Dyke, Mangla Dam - Muhammad Hamza Khalid; Tanzeela Yasmin; Badee Alshameri; Syed Muhammad Jamil; Waqas Hassan (Modeling Earth Systems and Environment, 2024)

Ultrasonic-assisted synthesis of CaCu3Ti4O12/reduced graphene oxide composites for enhanced photocatalytic degradation of pharmaceutical products: Ibuprofen and Ciprofloxacin - Mohsen Ahmadipour; Mohammad Rezaei Ardani; Mohsen Sarafbidabad; Nadhem Missaoui; Meenaloshini Satgunam; Ramesh Singh; Hamza Kahri; Ujjwal Pal; Ai Ling Pang; Muhammad Saqlain Iqbal; Renuka Garg; Anish Bhattacharya (Environmental Science and Pollution Research, 2024)

Genome-wide screening and evolutionary analysis of ZIP (ZRT–IRT like proteins) family in cowpea (Vigna unguiculata L.) - Arif Ullah; Zamarud Shah; Iqbal Munir; Hamza Iqbal; Muhammad Zulfiqar Ahmad; Warda Sultan; Afrasyab Khan (Genetic Resources and Crop Evolution, 2024)

Kinetic & thermodynamic studies of green fuel additive solketal from crude glycerol over metakaolin clay catalyst - Imtisal Zahid; Muhammad Ayoub; Muhammad Hamza Nazir; Farooq Sher; Rashid Shamsuddin; Bawadi bin Abdullah; Mariam Ameen (Biomass and Bioenergy, 2024)

Nitric oxide reduces cadmium uptake in wheat (Triticum aestivum L.) by modulating growth, mineral uptake, yield attributes, and antioxidant profile - Muhammad Nawaz; Muhammad Hamza Saleem; Muhammad Rehan Khalid; Baber Ali; Shah Fahad (Environmental Science and Pollution Research, 2024)

Melatonin alleviated cadmium accumulation and toxicity by modulating phytohormonal balance and antioxidant metabolism in rice - Raheel Munir; Muhammad Umair Yasin; Muhammad Afzal; Mehmood Jan; Sajid Muhammad; Nazia Jan; Chen Nana; Faisal Munir; Hamza Iqbal; Faiza Tawab; Yinbo Gan (Chemosphere, 2024)

Remote sensing and GIS based multi-criteria analysis approach with application of AHP and FAHP for structures suitability of rainwater harvesting structures in Lai Nullah, Rawalpindi, Pakistan - Rashid Ahmad; Hamza Farooq Gabriel; Farooq Alam; Riaz Zarin; Abdur Raziq; Muhammad Nouman; Hsu-Wen Vincent Young; Yuei-An Liou (Urban Climate, 2024)

First report on genotypic estimation of MRSA load in udder of nomadic sheep flocks affected with subclinical mastitis in Pakistan - Muhammad Jawad Sabir; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Muhammad Umar Javed; Farwa Anwaar (Research in Veterinary Science, 2024)

Green employee empowerment: The missing linchpin between green HRM and sustainable organizational performance - Muhammad Hamza Khan; Syaharizatul Noorizwan Muktar (Journal of Cleaner Production, 2024)

Modelling of debris-flow susceptibility and propagation: a case study from Northwest Himalaya - Hamza Daud; Javed Iqbal Tanoli; Sardar Muhammad Asif; Muhammad Qasim; Muhammad Ali; Junaid Khan; Zahid Imran Bhatti; Ishtiaq Ahmad Khan Jadoon (Journal of Mountain Science, 2024)

Sustainable production of glutamic acid by Enterobacter sp. strain isolated from cheese for potential protein biosynthesis: Optimization by Response Surface Methodology - Hamza Magaji; Shehu Muhammad Auwal; Rufa'i Nasir; Abdulrahman Itopa Suleiman; Shehu Usman; Ahmad Hussaini Jagaba (Bioresource Technology Reports, 2023)

An autoencoder-based stacked LSTM transfer learning model for EC forecasting - Abdullahi Uwaisu Muhammad; Hamza Djigal; Tasiu Muazu; Jibril Muhammad Adam; Abdoul Fatakhou Ba; Umar Sani Dabai; Sani Tijjani; Muhammad Sabo Yahaya; Aliyu Ashiru; Umar Muhammad Mustapha Kumshe; Saddam Aliyu; Faruwa Ajibola Richard (Earth Science Informatics, 2023)

RETRACTED ARTICLE: Assessing the impact of human capital, renewable energy, population growth, economic growth, and climate change policies on achieving the sustainable development goals - Hamza Akram; Jinchao Li; Muhammad Kahlid Anser; Muhammad Irfan; Waqas Ahmad Watto (Environmental Science and Pollution Research, 2023)

A bioactive chalcone from the aerial parts of Indigofera conferta Gillet - Maryam Isah; Salima Murtala; Sakynah Musa Abdullahi; Asmau Nasiru Hamza; Nasir Tajuddeen; Mu’ammar Lawal Dauda; Vuyisa Mzozoyana; Aliyu Muhammad Musa (Natural Product Research, 2023)

Case fatality rate and burden of snakebite envenoming in children – A systematic review and meta-analysis - Garba Iliyasu; Farouq M. Dayyab; Godpower C. Michael; Muhammad Hamza; Maryam A. Habib; José M. Gutiérrez; Abdulrazaq G. Habib (Toxicon, 2023)

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

Ring of Hope: A Novice’s Experience in a Cancer Centre - Muhammad Hamza Shah (Journal of Cancer Education, 2023)
The ringing of a bell has become an honored and cherished tradition in the realm of cancer survivorship care. As a medical student, I was initially unaware of this practice, but I have since gained a profound appreciation for its deep significance and emotional potency. Through the act of ringing the bell, patients who have successfully completed their cancer treatment are able to mark the end of a gruelling journey, while also heralding the start of a new and hopeful chapter in their lives.

Pilot Study Evaluating Cross-Disciplinary Educational Material to Improve Patients’ Knowledge of Palliative Radiation Therapy - Faryal Rizvi; Mark R. Korst; Meredith Young; Muhammad Hamza Habib; Joshua A. Kra; Ankit Shah; Tina M. Mayer; Biren Saraiya; Olga F. Jarrín; Malcolm D. Mattes (Journal of Cancer Education, 2023)

Prophylactic effects of dietary Isochrysis galbana on immersion-challenged red hybrid tilapia (Oreochromis spp.) with Streptococcus agalactiae by spleen-NMR-metabolomics - Muhammad Safwan Ahamad Bustamam; Khozirah Shaari; Chong Chou Min; Md Shirajum Monir; Hamza Ahmed Pantami; Intan Safinar Ismail (Aquaculture International, 2023)

Correction: KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)

ADU-Net: Semantic segmentation of satellite imagery for land cover classification - Muhammad Talha; Farrukh A. Bhatti; Sajid Ghuffar; Hamza Zafar (Advances in Space Research, 2023)

A prospective observational phase IV study on effectiveness of animal derived polyclonal antibody antivenoms against West African carpet viper (Echis romani) induced coagulopathy and mortality - Titus B. Dajel; Saidu B. Abubakar; Nasiru M. Dan-Amarya; Nyam A. Azi; Salisu Mu'azu; Muhammad Hamza; Garba Iliyasu; Muhammad Y. Gwarzo; Abdulrazaq G. Habib (Toxicon, 2023)

Attenuative effect of astilbin on polystyrene microplastics induced testicular damage: Biochemical, spermatological and histopathological-based evidences - Arooj Rizwan; Muhammad Umar Ijaz; Ali Hamza; Haseeb Anwar (Toxicology and Applied Pharmacology, 2023)

Evidence and Molecular Characterization of Multidrug Resistant Staphylococcus aureus Isolated From Equines in Pakistan - Farwa Anwaar; Muhammad Ijaz; Hamza Rasheed; Syed Faizan Ali Shah; Syed Ali Raza Haider; Muhammad Jawad Sabir (Journal of Equine Veterinary Science, 2023)

A comparative analysis of second-generation biofuels and its potentials for large-scale production in arid and semi-arid regions - Yassir Makkawi; Muhammad Khan; Fatemeh Hassan Pour; Omar Moussa; Baraa Mohamed; Hamza Alnoman; Yehya Elsayed (Fuel, 2023)

Hydrogen Peroxide Promotes Terminal Heat Stress Recovery in Wheat by Strengthening Leaf Physiological Functioning - Muhammad Sarwar; Muhammad Farrukh Saleem; Siraj Ahmed; Hamza Maqsood; Saddam Hussain; Muhammad Ashfaq Wahid; Muhammad Kashif Munir; Muhammad Zafar; Najeeb Ullah; Ali Khoddami (Journal of Plant Growth Regulation, 2023)

KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)
Super Basmati is an elite variety with extra-long grains and superior quality but its yield is severely affected by water stress. Recombinant inbred lines (RILs) developed from the cross of Super Basmati and IR55419-04 (a coarse grained variety with high yield potential) were used to identify and map yield-related quantitative trait loci (QTLs) under normal field conditions. Genotypes for 244 KASP markers were obtained from 188 F 9 RILs and a linkage map constructed of 1369.4 cM, with average marker interval of 10.5 cM. Eleven agronomic traits were phenotyped in RILs and parents. Composite interval mapping and inclusive composite interval mapping model identified 21 common QTLs related to nine agronomic traits; of the QTLs identified, twelve mapped at novel positions. LOD scores ranged from 2.51 for number of filled grains ( qFG1.1 ) to 16.8 for plant height ( qPH1.1 ). Four major effect QTLs could explain 20% of variation related for plant height, hundred-grain weight and grain width. Alleles from IR55419-04 improved grain filling, grain weight and grain width, while alleles from Super Basmati contributed to longer grains, panicles and flag leaves. Putative candidate genes were identified for 18 yield-related QTLs. These results validate the use of KASP genotyping for QTL mapping of yield-related traits in a bi-parental segregating population. SNPs in the QTLs identified in this study can be used in marker assisted selection for yield components to improve Basmati rice.

Geotechnical properties of problematic expansive subgrade stabilized with guar gum biopolymer - Muhammad Hamza; Zhihong Nie; Mubashir Aziz; Nauman Ijaz; Chuanfeng Fang; Muhammad Usman Ghani; Zain Ijaz; Sadaf Noshin; Muhammad Salman (Clean Technologies and Environmental Policy, 2023)

Seismic Performance of Helical Piles—A State of the Art Literature Review - Hamza Ahmad Qureshi; Muhammad Safdar (Arabian Journal of Geosciences, 2023)

Comparison of snakebite in children and adults in Nigeria - Garba Iliyasu; Titus B. Dajel; Saidu B. Abubakar; Nyam Agwom Azi; Nasiru M. Danamarya; Olusegun A. Obateru; Abdulhakim M. Dayyab; Muhammad Hamza; Olatunde A. Alabi; Abdulrazaq G. Habib (Toxicon, 2023)

Performance of the 20 minutes Whole Blood Clotting Test in detection, monitoring and antivenom therapy of West African Carpet viper (Echis romani) envenoming in resource constrained settings in Nigeria - Muhammad Hamza; Titus B. Dajel; Saidu B. Abubakar; Auwalu S. Hamza; Hadiza L. Abdullahi; Garba Iliyasu; Abdulrazaq G. Habib (Toxicon, 2023)

Manipulation of plant growth stimulants on plant morphology, phenology, and disease incident of Gossypium hirsutum L. under various thermal regimes - Muhammad Sarwar; Muhammad Farrukh Saleem; Basharat Ali; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Ashfaq Wahid; Muhammad Shahid; Theodore M. Mwamba; Bilal Ahmad Khan; Hamza Maqsood (Arabian Journal of Geosciences, 2023)

An effective deep learning model for ship detection from satellite images - Aaqib Mehran; Samabia Tehsin; Muhammad Hamza (Spatial Information Research, 2023)

Genetically engineered microorganisms for environmental remediation - Hamza Rafeeq; Nadia Afsheen; Sadia Rafique; Arooj Arshad; Maham Intisar; Asim Hussain; Muhammad Bilal; Hafiz M.N. Iqbal (Chemosphere, 2023)

Investigating the textural and physico-mechanical response of granites to heat treatment - Hamza Khan; Muhammad Sajid (International Journal of Rock Mechanics and Mining Sciences, 2023)

Immunomodulatory effects of Isochrysis galbana incorporated diet on Oreochromis sp. (red hybrid tilapia) via Sera-1H NMR metabolomics study - Muhammad Safwan Ahamad Bustamam; Hamza Ahmed Pantami; Khozirah Shaari; Chong Chou Min; Ahmed Mediani; Intan Safinar Ismail (Fish & Shellfish Immunology, 2023)

Statistical interpolation and spatial mapping of geotechnical soil parameters of District Sargodha, Pakistan - Waqas Hassan; Muhammad Fazal Raza; Badee Alshameri; Arfan Shahzad; Muhammad Hamza Khalid; Muhammad Naqeeb Nawaz (Bulletin of Engineering Geology and the Environment, 2023)

Formation and activity of NLRP3 inflammasome and histopathological changes in the lung of corpses with COVID-19 - Morteza Gholaminejhad; Mehdi Forouzesh; Babak Ebrahimi; Seyed Amirhosein Mahdavi; Seyed Davood Mirtorabi; Amirreza Liaghat; Seyed Jalil Monabati; Muhammad Obaid Hamza; Gholamreza Hassanzadeh (Journal of Molecular Histology, 2022)

Strengthening potential of xanthan gum biopolymer in stabilizing weak subgrade soil - Muhammad Hamza; Zhihong Nie; Mubashir Aziz; Nauman Ijaz; Zain Ijaz; Zia ur Rehman (Clean Technologies and Environmental Policy, 2022)

Asymptomatic populus alba: a tree serving as a reservoir of begomoviruses and associated satellites - Roma Mustafa; Muhammad Hamza; Atiq Ur Rehman; Hira Kamal; Muhammad Nouman Tahir; Shahid Mansoor; Brian E. Scheffler; Rob W. Briddon; Imran Amin (Australasian Plant Pathology, 2022)

Neurotoxic effects of environmental contaminants—measurements, mechanistic insight, and environmental relevance - Nadia Afsheen; Sadia Rafique; Hamza Rafeeq; Kanwal Irshad; Asim Hussain; Zille Huma; Vineet Kumar; Muhammad Bilal; Lotfi Aleya; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

Acceleration of flow modeling using a freeware 2D GPU-shallow water equations code - Prince Mahmood; Sajjad Haider; Hamza Farooq Gabriel; Muhammad Shahid; Zain Syed (Arabian Journal of Geosciences, 2022)

Host plants of Phenacoccus solenopsis (Tinsley) affect parasitism of Aenasius bambawalei (Hayat) - Hamza Younas; Muhammad Razaq; Muhammad Omer Farooq; Rabia Saeed (Phytoparasitica, 2022)

Reducing nutrient uptake in okra weeds by suppressing their population through alligator weed compost mulch for better pod yield and quality - Asif Tanveer; Muhammad Sarwar; Muhammad Shahbaz Asghar; Muhammad Farrukh Saleem; Hamza Maqsood; Basharat Ali; Muhammad Kashif Munir; Muhammad Arshad; Rao Muhammad Ikram; Nabeel Ahmad Ikram; Muhammad Rizwan (Arabian Journal of Geosciences, 2022)

Strengthening of high plastic clays by geotextile reinforcement - Muhammad Hamza; Mubashir Aziz; Wang Xiang; Muhammad Waqas Younis; Zhihong Nie; Muhammad Ali; Mudassar Dilawar; Ashiru Mohammed; Farhad Ali; Rahat Ullah; Mazhar Yasin; Atteq Ur Rehman (Arabian Journal of Geosciences, 2022)

Comparative study of various interpretative methods of the pile load test - Ahrar Mahmood; Badee Alshameri; Muhammad Hamza Khalid; S. Muhammad Jamil (Innovative Infrastructure Solutions, 2022)

Bacterial prediction using internet of things (IoT) and machine learning - Hamza Khurshid; Rafia Mumtaz; Noor Alvi; Ayesha Haque; Sadaf Mumtaz; Faisal Shafait; Sheraz Ahmed; Muhammad Imran Malik; Andreas Dengel (Environmental Monitoring and Assessment, 2022)

Dendritic Cell–Targeted Therapies to Treat Neurological Disorders - Asim Hussain; Hamza Rafeeq; Nimra Munir; Zara Jabeen; Nadia Afsheen; Khalil ur Rehman; Muhammad Bilal; Hafiz M. N. Iqbal (Molecular Neurobiology, 2022)

Subtractive Proteomics and Immuno-informatics Approaches for Multi-peptide Vaccine Prediction Against Klebsiella oxytoca and Validation Through In Silico Expression - Qudsia Yousafi; Humaira Amin; Shabana Bibi; Rafea Rafi; Muhammad S. Khan; Hamza Ali; Ashir Masroor (International Journal of Peptide Research and Therapeutics, 2021)

Functional identification of G. hirsutum genes for their role in normal plant development and resistance against Verticillium dahliae using virus-induced gene silencing - Roma Mustafa; Muhammad Javed Iqbal; Muhammad Hamza; Atiq Ur Rehman; Ismail Buzdar; Hira Kamal; Shahid Mansoor; Imran Amin (European Journal of Plant Pathology, 2021)

Rainfall forecasting in upper Indus basin using various artificial intelligence techniques - Muhammad Hammad; Muhammad Shoaib; Hamza Salahudin; Muhammad Azhar Inam Baig; Mudasser Muneer Khan; Muhammad Kaleem Ullah (Stochastic Environmental Research and Risk Assessment, 2021)

Role of nanotechnology in animal production and veterinary medicine - Ahmad Ali; Muhammad Ijaz; Yasir Razzaq Khan; Hina Afzal Sajid; Kashif Hussain; Ameer Hamza Rabbani; Muhammad Shahid; Omer Naseer; Awais Ghaffar; Muhammad Anas Naeem; Muhammad Zeeshan Zafar; Amir Iftikhar Malik; et al. (Tropical Animal Health and Production, 2021)

Occurrence, distribution, and pollution indices of potentially toxic elements within the bed sediments of the riverine system in Pakistan - Javed Nawab; Zia Ud Din; Riaz Ahmad; Sardar Khan; Mazhar Iqbal Zafar; Shah Faisal; Waleed Raziq; Hamza Khan; Zia Ur Rahman; Abid Ali; Muhammad Qayash Khan; Sajid Ullah; et al. (Environmental Science and Pollution Research, 2021)

Assessing the potential and hydrological usefulness of the CHIRPS precipitation dataset over a complex topography in Pakistan - Muhammad Shahid; Khalil Ur Rahman; Sajjad Haider; Hamza Farooq Gabriel; Abdul Jabbar Khan; Quoc Bao Pham; Babak Mohammadi; Nguyen Thi Thuy Linh; Duong Tran Anh (Hydrological Sciences Journal, 2021)

Synergistic Effect of Urease and Nitrification Inhibitors in the Reduction of Ammonia Volatilization - Asim Hussain; Nazish Jahan; Zara Jabeen; Khalil Ur Rehman; Hamza Rafeeq; Muhammad Bilal; Hafiz M. N. Iqbal (Water, Air, & Soil Pollution, 2021)

The intracontinental High Atlas belt: geological overview and pending questions - Hamza Skikra; Khalid Amrouch; Abderrahmane Soulaimani; Rémi Leprêtre; Muhammad Ouabid; Jean-Louis Bodinier (Arabian Journal of Geosciences, 2021)

Application of precipitation products for flood modeling of transboundary river basin: a case study of Jhelum Basin - Muhammad Umer; Hamza Farooq Gabriel; Sajjad Haider; Ammara Nusrat; Muhammad Shahid; Muhammad Umer (Theoretical and Applied Climatology, 2021)

Impact of Urbanization on Groundwater Levels in Rawalpindi City, Pakistan - Faraz ul Haq; Usman Ali Naeem; Hamza Farooq Gabriel; Noor Muhammad Khan; Ijaz Ahmad; Habib Ur Rehman; Muhammad Awais Zafar (Pure and Applied Geophysics, 2021)

Correction to: Effect of Endoxylanase and Iron Oxide Nanoparticles on Performance and Histopathological Features in Broilers - Hamza Rehman; Muzamal Akram; Mubin Mustafa Kiyani; Muhammad Talha Yasin; Abdul Ghani; Javed Iqbal Saggu; Syed Sajid Hussain Shah; Zafar Mahmood Khalid; Syed Ali Imran Bokhari (Biological Trace Element Research, 2021)

Investigating the potential of different jute varieties for phytoremediation of copper-contaminated soil - Muhammad Hamzah Saleem; Muzammal Rehman; Muhammad Kamran; Javaria Afzal; Hamza Armghan Noushahi; Lijun Liu (Environmental Science and Pollution Research, 2020)

Inhibition of Hyperuricemia and Gouty Arthritis in BALB/c Mice Using Copper Oxide Nanoparticles - Mubin Mustafa Kiyani; Hamza Rehman; Mir Arif Hussain; Saira Jahan; Muhammad Afzal; Irum Nawaz; Tariq Mahmood; Syed Ali Imran Bokhari (Biological Trace Element Research, 2020)

Dynamics of AB-DTPA-extractable Zn in high and low limed calcareous soils amended with biochar and farmyard and poultry manures - Abida Saleem; Dost Muhammad; Mumtaz Khan; Qudrat Ullah Khan; Muhammad Rizwan; Salma Shaheen; Hamza Noor; Shiza Gul; Muhammad Daud Khan; Shafaqat Ali (Arabian Journal of Geosciences, 2020)

Multiple alphasatellites associated with Papaya leaf curl virus and Croton yellow mosaic betasatellite in Croton bonplandianus: first identification of Ageratum yellow vein Singapore alphasatellite in Pakistan - Roma Mustafa; Muhammad Hamza; Muhammad Nouman Tahir; Hira Kamal; Muhammad Zuhaib Khan; Atiq ur Rehman; Brian E. Scheffler; Rob W. Briddon; Shahid Mansoor; Imran Amin (European Journal of Plant Pathology, 2019)

Technetium-99m labeled Ibuprofen: Development and biological evaluation using sterile inflammation induced animal models - Naeem-Ul-Haq Khan; Syed Ali Raza Naqvi; Hamza Sohail; Samina Roohi; Muhammad Asghar Jamal (Molecular Biology Reports, 2019)

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability - Regie Lyn P. Santos-Cortez; Valeed Khan; Falak Sher Khan; Zaib-un-Nisa Mughal; Imen Chakchouk; Kwanghyuk Lee; Memoona Rasheed; Rifat Hamza; Anushree Acharya; Ehsan Ullah; Muhammad Arif Nadeem Saqib; Izoduwa Abbe; et al. (Human Genetics, 2018)

Development of a flood forecasting system using IFAS: a case study of scarcely gauged Jhelum and Chenab river basins - Aamir Shahzad; Hamza Farooq Gabriel; Sajjad Haider; Ammara Mubeen; Muhammad Junaid Siddiqui (Arabian Journal of Geosciences, 2018)

Erratum to: Recent developments in immobilizing titanium dioxide on supports for degradation of organic pollutants in wastewater-A review - M. H. Alhaji; K. Sanaullah; A. Khan; A. Hamza; A. Muhammad; S. I. Mustapha; A. R. H. Rigit; S. A. Bhawani (International Journal of Environmental Science and Technology, 2017)

Recent developments in immobilizing titanium dioxide on supports for degradation of organic pollutants in wastewater- A review - M. H. Alhaji; K. Sanaullah; A. Khan; A. Hamza; A. Muhammad; M. S. Ishola; A. R. H. Rigit; S. A. Bhawani (International Journal of Environmental Science and Technology, 2017)

Assessment of radiological hazard of NORM in Margalla Hills limestone, Pakistan - Muhammad Ali; Aziz Ahmed Qureshi; Abdul Waheed; Muzahir Ali Baloch; Hamza Qayyum; Muhammad Tufail; Hameed Ahmed Khan (Environmental Monitoring and Assessment, 2012)